PENGELOLAAN PEMBELAJARAN IPA TEMATIK MODEL PAIKEM DI MADRASAH IBTIDAIYAH NEGERI TANDUK AMPEL KEBUPATEN BOYOLALI - MAHMUDI , MAHMUDI (2011)
Research purposes are: (1) to describe the planning caracteristics of thematic natural science teaching learning PAIKEM model in Tanduk Goverment Elementary for Islamic School Ampel Boyolali Regency, (2) to describe the implementation characteristics of thematic natural science teaching learning PAIKEM model in Tanduk Goverment Elementary of Islamic School Ampel Boyolali Regency, and (3) to describe the evaluation characteristics of thematic natural science teaching learning PAIKEM model in Tanduk Goverment Elementary for Islamic School Ampel Boyolali Regency. The focuses on, "How is the management characteristic of thematic natural science teaching learning PAIKEM model in Tanduk Goverment Elementary for Islamic School Ampel Boyolali Regency. The research has done in Tanduk Goverment Islamic School Ampel Boyolali Regency while the subjects are the school head master, curriculum departement, public relation departemen, teacher in class thr ee, school committe, students' parent, and the student. The research uses qualitative approach whit etnographic strategy, considering: (1) Tanduk Goverment Elementary for Islamic School is a core school of some Islamic school weated in Ampel Boyolali Regency. (2) This school uses a different system management with other school that is applying thematic approach and PAIKEM model. To get data, the researcher uses the methode as follows: analizyng syllabus dokument, lesson plan, and assesment sheet. Interviering with the head master, curriculum section, public relation section, the third grade's teachers, Islamic school committe, the leaner trustee, and the leaners. Observasing teaching learning process in third grade. The data analysis will be conducted in tree stage, there are: data reduction, data presentation, and conclution/verification. There are several important isssues related to sub focus of research, they as the result of this research, are: (1) teaching learning plan including syllabus and lesson plan characterizing thematic natural science teaching learning using PAIKEM model whit maximum class management, (2) the teaching learning implementation is based on the lesson plan beginiing whit an interesting pre- activity, there is communication between students and teacher, although there is a teacher's expression or teacher's action that frighten his and her students (make his and her students affraid), and (3) the caracteristic of teaching learning assesment done comprehensively and continously.